Determining Mocaf Production Quantity Using Sugeno's Fuzzy Model: Analyzing Slicing Machine Effectiveness and Raw Material Forecasting in SMEs - Santosa, Sesar Husen Santosa; Hidayat, Agung Prayudha Hidayat; Siskandar, Ridwan Siskandar (JURNAL TEKNIK INDUSTRI, 2025)
The production of Mocaf flour in small and medium enterprises (SMEs) is influenced by the effectiveness of cassava slicing machines in ensuring the availability of raw materials during the fermentation process. Slicing cassava is often problematic because the tools used are not of good quality, causing the cassava to crumble. This problem requires the identification of the effectiveness of cassava slicing machines in Mocaf flour production. The effectiveness of the cassava slicing machine can be measured using the Overall Equipment Effectiveness (OEE) method, and the values obtained are availability = 91%, Performance = 78%, Quality Yield = 0.99, and OEE = 0.71. The results of the selected forecasting, namely Double Moving Average with n = 2, MAPE = 4,54 %, show that the predicted production of cassava slices is 1428.57 kg. The OEE results and production forecasting then become the basis for developing the Sugeno fuzzy model to determine the amount of mocaf flour production in SMEs. The results of Sugeno fuzzy defuzzification with the OEE membership set production forecasting and triangular membership type showed that the mocaf flour production was 450 kg. Based on the production of mocaf flour of 450 kg, with a yield of 28%, the cassava raw material that must be ordered from the supplier is 1428,57 kg.